Compatibility with silver electrode and microwave dielectric properties of low firing CaWO4-2Li2WO4 ceramics. (May 2017) - Zhou, Huanfu; Huang, Jin; Tan, Xianghu; Wang, Nan; Fan, Guangchao; Chen, Xiuli
Graphical abstract: Highlights: CaWO4 -2Li2 WO4 low-firing material was prepared by solid state reaction method. CaWO4 -2Li2 WO4 ceramic exhibited good properties of Q   ×   f  = 62400 GHz, εr  = 6.1 and τf  = −100.1 ppm/°C. CaWO4 -2Li2 WO4 ceramic has a chemical compatibility with Ag, indicating its application in LTCC devices. Abstract: A low firing microwave dielectric ceramic with the composition of CaWO4 -2Li2 WO4 was prepared by the solid-state reaction method. The phase composition, microstructure and microwave dielectric properties of ceramics were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM) and network analyzer. The CaWO4 -2Li2 WO4 ceramics sintered at 740 °C for 4 h possessed the superior comprehensive performance with relative permittivity ( εr ) of 6.10, quality factor ( Q   ×   f ) of 62400 GHz and temperature coefficient of resonant frequency ( τf ) of −100.1 ppm/°C. The CaWO4 -2Li2 WO4 dielectric ceramics were chemically compatible with silver (Ag) electrode, indicating that CaWO4 -2Li2 WO4 ceramics might be a promising candidate for low temperature co-fired ceramic (LTCC) devices.